Villa Resort Danau Diatas Dengan Prinsip Desain Frank Lloyd Wright - Agung Kurniawan; Mira Dharma Susilawaty; Wahyu Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Lake Diatas is a lake that has a beautiful natural scenery, even some newspapers preach that the beauty of the lake Diatas is not less beautiful with foreign countries, so there are enough tourists who visit this lake. With a very beautiful natural beauty, this place does not have adequate facilities to pamper and make visitors more comfortable to visit enjoy the beauty of the lake. One of the facilities that is necessary to support the lake area above is a decent residential facility. As with the construction of Villa Resort occupancy, the view directly to the lake. Villa Resort is an area of accommodation with a villa unit with a main function in the form of lodging equipped with supporting facilities in the form of entertainment, recreation, relaxation and sports activities. The design principles of Frank Lloyd Wright are as follows: The simplicity and serenity, the expression of personality, the correlation with nature, natural colors, the nature of materials and spiritual integrity. Of the six design principles are very suitable for the design of Villa Resort in the lake Diataskeywords : Villa Resort Lake Diatas, Frank Lloyd Wright Design Principles